Academic tourism in Barcelona (Spain) in the COVID-19 era - Carlota Culubret; Ane González; Montserrat Iglesias; Sara Moreno; Víctor Roigé (REGION, 2022)
Academic stays at higher education institutions located outside students' usual environment for less than a year have become increasingly popular. The research reported in this article aimed to examine the current situation of international academic tourism in the region of Barcelona (Spain). The main objectives were to profile academic tourists, to analyse the impact of the COVID-19 pandemic on inbound academic tourism flows, and to explore the outcomes of academic travel experiences. Following a mixed-methods approach, two focus groups and three in-depth interviews were conducted to collect data from both a supply and demand perspective, in addition to a survey designed for international students. A total of 132 questionnaires were analysed by means of descriptive statistics and through chi-square and ANOVA tests. Qualitative data was processed by means of categorisation and content analysis using QDA Miner. The main results indicate that academic tourism has positive sustainable impacts and is conducive to transformational experiences. Tourists' profile has been identified and the effects of the pandemic have been pinpointed. Due to COVID-19, academic tourism flows experienced a serious decline and the satisfaction degree with the academic travel experience was lower. Nonetheless, most of the respondents would recommend Barcelona as an academic destination.
Keywords: 330